Effects of multicomponent exercise training program on biochemical and motor functions in patients with alzheimer’s dementia - Chortane, Oussama Gaied (2022)
The aim of this study was to examine the effects of a multicomponent exercise training program on motor function and biochemical markers in patients with Alzheimer’s-type dementia. Twenty patients with Alzheimer disease, divided into the intervention group (IG; aged 84 ± 3.1 years) and the control group (CG; aged 86 ± 2.6 years) were included in this study. The intervention group was enrolled into an exercise training program for three months (two sessions of 60 min per week). The CG was instructed to follow their daily rhythm of life (e.g., rest, reading) without a physical training program. After 3 months of participation in a multicomponent exercise program, gait speed, balance and walking parameters were all improved in the intervention group as measured with the Berg Balance Scale, the Tinetti test, the 6-min walking test and the timed up and go test (p < 0.05 for all; percentage range of improvements: 3.17% to 53.40%), except the walking while talking test, and biochemical parameters were not affected (p > 0.05). Our results demonstrate that exercise improves postural control, aerobic capacity and mobility functions in patients with Alzheimer disease. Physical exercise is a safe and effective method for treating physical disorders in patients with Alzheimer’s disease and can easily be integrated in various programs for the management of Alzheimer disease.